DIGLOT PICTURE STORYBOOK BASED ON MALUKU CONTENT AND ITS RELEVANCE FOR YOUNG LEARNERS’ LITERACY - Threesje R Souisa; Jenny Lekatompessy; Marcy Ferdinandus (JURNAL TAHURI, 2020)
Providing young learners with variety story books to develop their literacy is importance to be done by considering their interest and learning preferences, and mrany of children storybook written in English in nowadays. Therefore young learners like to read English children story book since they are in the early stage. Unfortunately in the EFL frame, many children story book less to touch local content materials. Folklore is one of the oral traditions that are told for young learners with the purpose that they will know about their culture and tradition and it can be preserved with meaningful ways in EFL teaching and learning process. Much folklore are written in English and mostly talked about the culture of that language because it is believed that young learners can acquire this language easy both in spoken and written language. Unfortunately those folklores lack to present the local content of EFL context. One of the ways to facilitate young learners loves their culture by inserting local content materials in picture story books. Through reading vary children story books can arise young learners’ interest to master this language naturally. Diglot picture story book is a kind of children story book contain two languages and supporting with interesting pictures. It is believed as one of the meaningful ways that young learners can engage and explore deeply about the story with their own experiences .This study is aimed at describing diglot picture story book based on Maluku content and its relevance for young learners’ literacy.